Використання зоонімів для створення сатиричного ефекту - Горбач, Олена; Gorbach, Olena (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті визначено специфіку використання літературних зоонімів в українських прозових художніх творах сатирично-гумористичного спрямування; проаналізовано їх лексико-семантичні й виражальні можливості, сатиричний потенціал, несподівані авторські експерименти. За структурними особливостями в аналізованих сатирично- гумористичних творах домінують структурно однослівні ЛЗ з ідентифікаторами (детермінативами), котрі характеризуються максимальною наближеністю до кличок. The article outlines the specific use of literary prose zoonims in Ukrainian works of literature of satire and humorous direction; analysis of lexical-semantic and expressive powers, satirical potential copyright unexpected experiments.Literary and аrtistic zoonymyya and subgroups of zoonims is «main chain of artistic text in the organization and method of how named character and they have stylistic significant resources». For structure features in analyzed satiric-humoristic texts are dominated structural one-word zoonims with characterized by determinatyvy, which are closed to klychka (connection with traditional onomasticon). Zoonyms of Ukrainian satiric-humoristic texts of ending XX – beginning XXI century have individual, connotation and motivation. Literary zoonims are used for reflection genre- ideological type of writer; indirectly characterize heroes; make satirical effect through parallels, association, contrast; give ability to reflect the colour of some century.
Application of Zoonims for Making Satirical Effect.
Keywords: літературний зоонім; зоонімікон; ідентифікатори; кіноніми; феліноніми; фероніми; сатиричний ефект; literary zoonim; zoonimikon; kinonimy; felinonimy; feronimy; satirical effect